Flat Shape Concept in Kaddo’ Masingkulu: An Exploration of Bugis-Makassar Culture-Based Ethnomathematics in Strengthening Culturally Responsive Teaching - Mutmainna Mutmainna; Gunarhadi Gunarhadi; Karsono Karsono; Zulfahmi Mustapa Rapa (Electronic Journal of Education, Social Economics and Technology, 2025)
This study explores the geometric concepts embedded in Kaddo’ Masingkulu, a triangular-shaped traditional cake rooted in Bugis-Makassar culture, and its potential in supporting Culturally Responsive Teaching (CRT) through an ethnomathematical lens. The research aims to (1) examine the flat shape properties reflected in Kaddo’ Masingkulu and (2) analyze the integration of Bugis-Makassar cultural elements into mathematics teaching to enhance conceptual understanding and cultural awareness. Employing a qualitative exploratory case study design, data were collected from 2 teachers, 10 students, and 2 cultural practitioners in an elementary school in Takalar Regency, using interviews, classroom observations, and document analysis. Thematic analysis revealed that the triangle in Kaddo’ Masingkulu carries both mathematical and symbolic meanings-representing harmony among humans, nature, and the divine. Students demonstrated improved understanding of flat shapes, including triangles, parallelograms, and trapezoids, by engaging with culturally familiar contexts. Teachers utilized visual, narrative, and project-based strategies to connect geometry content with students' everyday experiences. The integration of ethnomathematical content not only reduced misconceptions in geometry but also promoted student motivation and confidence. The study concludes that leveraging local cultural artifacts such as Kaddo’ Masingkulu enhances the contextualization of abstract mathematical concepts and affirms learners’ cultural identities. These findings imply the need for culturally grounded instructional models in mathematics education and highlight CRT as a viable pedagogical framework for multicultural classrooms.